Stochastic Time Series and Possibilities of their Use for Selected Modal Characteristics Determination of Mechanical Structures - Bohus Leitner (Communications - Scientific letters of the University of Zilina, 2001)
The paper deals with the possibilities of using mathematical apparatus of a stochastic time series for stochastic systems description and modeling, especially mechanical ones. Its purpose is to briefly characterise fundamental terms and equations of mathematical apparatus of time series, to describe the algorithm of a statistically adequate discrete model of a stochastically dynamic system to develop relationship between parameters of discrete and continuous modelsand to show some possibilities of developed strategy applications for solution of selected modal characteristics of mechanical structures.